A narrative review of the impact of forest rehabilitation programs on soil quality in Peninsular Malaysia - Karam, D.S.; Ibrahim, Z.; Rani, R.; Wahid, A.R.A.; Kadir, Z.A.; Salleh, M.S.A.; Abdul-Hamid, H.; Rajoo, K.S.; Ibrahim, M.H.M.; Azhar, M.A.A.; Zulperi, D.; Abdu, A. (Malaysian Society of Soil Science, 2022)
The rehabilitation of forest areas is not new to Malaysia as forest replanting activities have been carried out throughout the country for years to meet the demand for woody and non-woody products as well as to nurture degraded forestland. Thus it is important for a soil to be evaluated to ascertain the degree to which rehabilitation activities have succeeded in restoring forest health, particularly in sustaining soil quality in rehabilitated forests. This review article aims to provide a corpus of information for forest managers and related agencies who work closely with forestry. The aim is to provide an overview on the importance of soil quality in measuring the success of forest rehabilitation programs. Research articles on the evaluation of soil properties at selected rehabilitated forests in Peninsular Malaysia were included in the review. The impact of forest rehabilitation in relation to soil properties comprising soil compaction, moisture, acidity, macronutrients, cation exchange capacity, microbial count, microbial enzymatic activity, and microbial biomass is discussed. Natural forest is used as a benchmark to see the effect of forest rehabilitation programs. Our review indicates that rehabilitated forests that were established earlier and have gone through a longer period of time have better soil quality compared to the soil of forests established later. This shows that rehabilitated forests are able to restore their soil quality and achieve fertility on par with natural forests, if given longer periods of time for recovery. Soil quality analyses should be done regularly to measure the extent of success in rehabilitation programs.